Mapping competitiveness with European data - Koch, Andreas; Castellani, Davide (Brussels, 2015)
"Europe needs improved competitiveness to escape the current economic malaise, so it might seem surprising that there is no common European definition of competitiveness, and no consensus on how to consistently measure it.